DESIGN OF A WEB-BASED POINT RECORDING SYSTEM AT SMK NEGERI 1 TAKENGON - Radinka Daffa (INFOKUM, 2023)
The Guidance and Counseling Website for Teachers is an online resource created with the express purpose of offering assistance and direction to teachers in carrying out their duties more successfully and improving their general well-being. This website attempts to offer pertinent materials, data, and counseling services catered to the unique requirements of instructors.Teachers frequently encounter a variety of difficulties in the increasingly difficult and complex educational environment, one of which is classroom management. This point-recording website was created to help teachers at SMK Negeri 1 Takengon capture students' points of failure more easily, avoiding data errors and enhancing the effectiveness and efficiency of their job.